The unconscious in Freud and Lacan (Research, Society and Development, 2024)
Psychoanalysis, initially proposed by Freud, arose from the observation, especially in hysterical women, of physical symptoms without organic causes. Freud listened to these patients and developed metapsychology, analyzing the dynamic, topological, and economic functioning of the psychic apparatus. Psychoanalysis evolved into different schools of thought, with notable figures like Lacan, who revisited Freud in 27 seminars, emphasizing the unconscious as structured by language. Thus, the aim of this research is to discuss and elaborate on the notions that underpin Freudian-Lacanian psychoanalysis, addressing the main differences in the construction of the unconscious concept between the two authors. The methodology used is a bibliographic review. Although based on Freud, Lacan offers a new perspective, updating psychoanalysis to reflect the complexities of the subject. Freud viewed the unconscious as having no verbal representation, while Lacan argues that the signifier represents the unconscious. Additionally, Lacan reinterprets the Oedipus Complex as a metaphorical process and introduces the concept of the "objet a," an object of desire that guides the subject's pursuit.